(untitled) (IITM Journal of Business Studies, 2024)
Japan is one of the developed nations in the Asian continent and holds enormous geographical and geopolitical importance in the cross-border movement of goods, services, people, and technology. Hence, it is substantial to analyse the impact of its de facto trade globalization and regulatory quality on ecological sustainability. Therefore, the study employs the autoregressive distributed lag (ARDL) model. Our results confirm that de facto trade globalization and regulatory quality have a positive impact on environmental sustainability, whereas economic growth has a negative impact on the sustainability of the ecology. The results validate that PHEH holds in Japan which means that it promotes environmentally safe trade and technology and its regulatory framework is firm enough in promoting clean trade. The relative decoupling situation is tantamount to an environmentally conscious society with rising economic performance